PENGARUH KUALITAS AUDIT, CORPORATE GOVERNANCE DAN LEVERAGE TERHADAP MANAJEMEN LABA - Gunawansyah, Hendri (JURNAL FAIRNESS, 2019)
This study aimed to prove the influence of audit quality, corporate governance and leverage on earnings management by using independent variables audit qulity, corporate governace (independent board, audit committees and ownership managerial) and leverage. The sampel in this study in a manufacturing company listed on the Indonesia stock exchange in 2010-2015 and consisted 50 companies. The data used secodary data obtained from financial from the website www.idx.co.id. Data was analyzed using multiple linear regression.The results indecated that The audit quality had notsignifikan influence on earnings management, The board commissioners had not signifikan influence on eranings management, The audit committe had a positif no signifikan on earnings management, The managerial ownership had a positif no signifikan on earnings management, The leverage had not influence on earnings management.